From micro to macro, nanotechnology demystifies acute pancreatitis: a new generation of treatment options emerges - Wei Du; Xinyue Wang; Yuyan Zhou; Wencheng Wu; Haojie Huang; Zhendong Jin (Journal of Nanobiotechnology)
Abstract Acute pancreatitis (AP) is a disease characterized by an acute inflammatory response in the pancreas. This is caused by the abnormal activation of pancreatic enzymes by a variety of etiologic factors, which results in a localized inflammatory response. The symptoms of this disease include abdominal pain, nausea and vomiting and fever. These symptoms are induced by a hyperinflammatory response and oxidative stress. In recent years, research has focused on developing anti-inflammatory and antioxidative therapies for the treatment of acute pancreatitis (AP). However, there are still limitations to this approach, including poor drug stability, low bioavailability and a short half-life. The advent of nanotechnology has opened up a novel avenue for the management of acute pancreatitis (AP). Nanomaterials can serve as an efficacious vehicle for conventional pharmaceuticals, enhancing their targeting ability, improving bioavailability and prolonging their half-life. Moreover, they can also exert a direct therapeutic effect. This review begins by introducing the general situation of acute pancreatitis (AP). It then discusses the pathogenesis of acute pancreatitis (AP) and the current status of treatment. Finally, it considers the literature related to the treatment of acute pancreatitis (AP) by nanomaterials. The objective of this study is to provide a comprehensive review of the existing literature on the use of nanomaterials in the treatment of acute pancreatitis (AP). In particular, the changes in inflammatory markers and therapeutic outcomes following the administration of nanomaterials are examined. This is done with the intention of offering insights that can inform subsequent research and facilitate the clinical application of nanomaterials in the management of acute pancreatitis (AP). Graphical Abstract